(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Amid the COVID-19 pandemic, most universities worldwide are forced to shift to distance learning and online learning. The purpose of this study is to examine the impact of information quality (IQ), system quality (SYQ) and service quality (SEQ) on perceived ease of use (PEOU) and perceived usability (PU), the impact of PEOU on PU, and the impact of PEOU and PU on behavioural intention to use e-learning. Questionnaires were distributed to the undergraduate students of Cihan University Erbil, and 238 valid questioners were returned. The results indicated the system characteristics, namely SYQ and IQ, significantly impacted PU. In contrast, SYQ and IQ had an insignificant effect on BI to use e-learning. Besides, SEQ had a significant impact on PEOU and an insignificant impact on PU. Additionally, PEOU significantly impacted PU, while PEOU and PU significantly impacted BI to use e-learning. The current research has shown that the intention of implementing an e-learning system for university students is to investigate the student’s intentions and objectives.